Effect of the Integrated Approach to Yoga Therapy on Stress-Related Anxiety Disorder of a Roller Skater - Dev Prakash (Recent Trends in Sports, 2025)
Anxiety and stress are common problems for competitive skaters, which frequently impairs their performance and general health. The Integrated Approach to Yoga Therapy (IAYT) offers a holistic intervention, addressing the physical, mental, and emotional dimensions of health. This study investigates the impact of IAYT on stress-related anxiety disorders in skaters, incorporating yoga postures (asanas), breathing techniques (pranayama), meditation, and relaxation practices. An 8-week intervention was conducted with 30 competitive skaters aged 14-25 years, divided into an experimental group practicing IAYT and a control group receiving standard care. The outcomes were evaluated using the Beck Anxiety Inventory (BAI), the Perceived Stress Scale (PSS), and performance ratings. The findings showed that the experimental group's experience of stress and anxiety was considerably lower than that of the control group. Coaches also reported marked improvements in focus, balance, and agility. Furthermore, the experimental group's members reported improved emotional control and a higher sense of wellbeing. The study highlights the significance of attending to athletes' mental health as a vital component in maximizing performance. The findings also highlight the potential of IAYT as an effective tool for managing stress-related anxiety disorders in skaters, enhancing their performance and quality of life. Future research should look at long-term effects and include larger, more diverse populations in order to validate these findings. This study underscores the value of integrating yoga therapy into athletic training regimens to foster resilience and holistic well-being.
Keywords: Anxiety; Meditation; asanas; pranayama; skater; stress; yoga nidra; yoga therapy